PRODUCTION OF MANGIUM (Acacia mangium) WOOD VINEGAR AND ITS UTILIZATION - Nurhayati, Tjutju; Roliadi, Han; Bermawie, Nurliani (Secretariat of Forestry Research and Development Agency, 2005)
Production of wood vinegar from mangium (Acacia mangium) wood bolts/pieces with their diameter of 3 17 cm, length of 30 67 cm, moisture content of 84.4%, and specific gravity of 0.52 conducted in a dome-shaped kiln with 1.2 m-capacity afforded a yield of 40.3%. The mangium wood vinegar was produced through condensation (cooling) of smoke/gas fractions released during the charcoaling (carbonization) process of mangium wood. The process could be regarded as an integrated production of wood vinegar and charcoal. The yield of wood vinegar combined with the resulting charcoal was 73.9% based on the dry weight of inputed mangium wood. Results of chromatography analysis on mangium wood vinegar as conducted in Japan revealed its organic acid content at 73.9 ppm, phenol content 8.09 ppm, methanol 3.34 ppm, acidity degree 4.91 ppm, and pH 3.89. Similar analysis on the mangium wood vinegar was conducted in Indonesias laboratories, and the results were comparable with those of Japan. Results of inhibition testings on particular microorganisms (i.e. Pseudomonas aerogjnosa, Stafi/ococms attreus, and Candidi albicans fimgz) indicated that the mangium wood vinegar could inflict antirnicrobe action on those microorganism with its effectiveness somewhat below that of liquid betel soap which could be purchased from drugstores. The experimental use of mangium wood vinegar at 3-5% concentration on ginger (Zingiber officinale var. white ginger) plants revealed significantly positive growth responses/ characteristics with respect to their height, leaf length, and sprout/ shoot development, in comparison with the untreated ginger plants (control). Such responses/characteristics were not significantly different from those using atoniks growth hormone. Likewise, the preliminary use of mangium wood vinegar at 2-percent concentration on teak (Teaonagrandis)plants, end stacks of Sborea Ieprosula and Swietenia mahagoni plants, and rice plants haveinflicted their favorable growth responses/ characteristics as well.